Top of Line Corrosion Behavior of X60 Pipeline Steel in CO2 Wet Gas Environment with High Cl- Concentration and High Gas Flow Rate - YU Yong, FAN Xue-hua, ZHANG Yu-nan, ZHU Jin-yang, CHEN Li-juan, LIU Zhao-wen, ZHANG Lei (Cailiao Baohu, 2021)
To clarify the top of line corrosion behavior of X60 pipeline steel at high CO2 wet gas and high flow rate condition with high Cl-, high speed wet gas loop system was used to conduct wet gas top of line corrosion simulation evaluation test of X60 pipeline steel.The wet top of line corrosion of X60 pipeline steel was evaluated by weight loss of samples before and after corrosion.The effects of different water content and different Cl- concentration on the wet top of line corrosion behavior of X60 pipeline steel were studied by means of scanning electron microscope(SEM), energy dispersive spectroscopy(EDS)and X-ray diffraction(XRD).Results showed that the salt particles were observed on the surface of X60 pipeline steel samples, indicating that there was scaling risk in a long service life under the conditions of 1 MPa CO2, 10 m/s wet gas flow rate condition with 130 000 mg/L and 170 150 mg/L Cl-, water content of 0.03% and 0.05%.When the Cl- content was 130 000 mg/L, the high water content promoted the corrosion of X60 pipeline steel.When the Cl- content reached 170 150 mg/L, the corrosion weight loss of X60 pipeline steel decreased with the increasing of water content.